The Meaning of Traditional Clothing of the Kajang People, Bulukumba Regency (Ethnographic Study of Communication) - Ikramullah Mahdi; Muliadi Mau; Arianto Arianto (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The location of this research in Tanah Toa Village is located in Kajang Kabupaten District, Bulukumba, South Sulawesi which still preserves the traditional clothing of the Kajang tribe. The research method used is qualitative descriptive with ethnographic methods of communication. The number of informants was 9 people obtained by purposive sampling technique. The stages in data collection techniques in this study are the observation method, in-depth interview method, literature method, and documentation method. The results showed that the meaning contained in the traditional clothing of the Kajang tribe has three aspects. First, based on the meaning of traditional clothing, it is a sign of cultural identity attached to the image of the Amata ethnic community and a sign of human life side by side with nature. Similarly, traditional clothing, namely Passau, Black Shirt (Pokko Shirt), Tope' Lelleng (Black Sarong) is a sign of obedience, an attitude of the simplicity of life that is communicated (Nonverbal). Second, the color of the spiritual symbol of the black spiritual symbol is a manifestation of human life, the birth of a human being from the realm of darkness to the end of his life also returns to the realm of darkness or is interpreted as always remembering life and death. Third, the cultural symbol of Attalla’s Kamase-Mase which is realized in every aspect of life through the attributes of leveling clothing means simplicity, simplicity, and equality for everyone before the Creator (Turiek Akra'na).